CHEST COMPUTED TOMOGRAPHY FINDINGS IN CANNABIS SMOKERS : SYSTEMATIC REVIEW - Sugih Laksono, Bella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: In contrast, cannabinoids and nicotine are chemically distinct compounds, with cannabinoids exhibiting a unique set of effects pertaining to aspects such as gene expression, inflammatory mechanisms, immunological modulation, and cellular energy and survival. Consequently, a comparison between the pulmonary effects of cannabis and tobacco consumption is crucial. As a sensitive and repeatable tool for quantifying the airway alterations and alveolar lung damage that are hallmarks of smoking-related emphysema and COPD, noninvasive lung imaging with HRCT scans has developed. In-depth analyses of HRCT images obtained from cannabis consumers were conducted in only two studies. The aim: This study review chest CT findings in cannabis smokers. Methods: For this systematic review, publications that were published from 2012 to 2023 were taken into account during the search process. This was achieved through the utilization of numerous online reference sources, such as Pubmed and SagePub. The decision was made to exclude review articles, previously published works, and incomplete works. Result: We obtained 54 articles from Pubmed and 76 from SagePub. We extracted were 2 article from Pubmed and 4 articles from SagePub. Conclusion: Research shows that patients can experience pneumothorax with bullae and blebs. Those who smoke marijuana can also experience emphysema and chronic bronchitis.